A New Historicist Reading of Reverse Colonization in H. G. Wells’ The War of the Worlds - Shokhan Mohammed; Ismael Mohammedfahmi (Zanco Journal of Humanity Sciences)
Literary movements are generally shaped by the historical events preceding and/or occurring during their establishment. Features of an author’s society find their way through a literary work and lie between the lines, even when not intended by the author. H. G. Wells’ The War of The Worlds (1898) is a vivid example of this type. The novel is written during a time when The British Empire has invaded several countries. Thus, the idea of colonization has filled the British people with invasion and its consequences. The difference, however, is highlighted by Wells through depicting a reverse colonization of England by aliens from Mars. The Martins’ representation portrays the justifications which imperialists and their proponents used in order to moralize and authenticate their actions.